2013
DOI: 10.1080/02699931.2013.772047
|View full text |Cite
|
Sign up to set email alerts
|

Mood states determine the degree of task shielding in dual-task performance

Abstract: Current models of multitasking assume that dual-task performance and the degree of multitasking are affected by cognitive control strategies. In particular, cognitive control is assumed to regulate the amount of shielding of the prioritised task from crosstalk from the secondary task. We investigated whether and how task shielding is influenced by mood states. Participants were exposed to two short film clips, one inducing high and one inducing low arousal, of either negative or positive content. Negative mood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Both sets of analyses had enough power to detect effect sizes from similar studies in this literature; a posthoc power analysis indicated that we had 80% power to detect a partial eta squared of 0.06-0.10, depending on the specific analysis. This is within the same range as effect sizes reported in the mood/CF literature (e.g., Wang, Chen, & Yue, 2017;Zwosta et al, 2013;Nadler, Rabi, & Minda, 2010). There are several possible explanations for failing to reject the null hypothesis in this study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Both sets of analyses had enough power to detect effect sizes from similar studies in this literature; a posthoc power analysis indicated that we had 80% power to detect a partial eta squared of 0.06-0.10, depending on the specific analysis. This is within the same range as effect sizes reported in the mood/CF literature (e.g., Wang, Chen, & Yue, 2017;Zwosta et al, 2013;Nadler, Rabi, & Minda, 2010). There are several possible explanations for failing to reject the null hypothesis in this study.…”
Section: Discussionsupporting
confidence: 84%
“…However, this flexibility came at the cost of increased distractibility; that is, participants were better able to adapt to changes that occurred, but that came at the cost of being more susceptible to interference (Dreisbach & Goschke, 2004). A similar conclusion is supported by results from Zwosta et al (2013) who found that a positive mood induction increased vulnerability to interference in a task switching protocol. Phillips and colleagues (2002) found that those in a happy mood were significantly slower on a switching condition of a traditional Stroop task, and López-Benítez et al (2017) found that trait positive mood did not influence task switching.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Negative mood, in turn, has been reported to increase top-down control, as in states of dysphoria induced by acute tryptophan depletion in remitted depressed patients (Booij et al 2005). Along the same lines, inducing negative mood increases the shielding of a prioritized task against competing tasks, as indicated by a reduction of cross talk between tasks (Zwosta et al 2013). Taken altogether, there is systematic evidence that positive-going mood drives metacontrol towards flexibility and some evidence that negative-going mood promotes persistence.…”
Section: Metacontrolmentioning
confidence: 93%
“…At the behavioral level emotion has been shown to influence multiple aspects of cognition including working memory [1], task shielding [2], attentional control [3], and visual attention [4,5,6]. At the neural level research has shown that the prefrontal cortex (PFC) is involved in emotional processing during cognitive task completion; see [7,8] for recent compressive reviews of this research area.…”
Section: Introductionmentioning
confidence: 99%